Antigenic variation in Trypanosoma vivax. Isolation of a serodeme - Barry, J.D.; Gathuo, H. (Cambridge University Press, 1984)
Studies of antigenic variation inTrypanosoma vivaxhave been hindered by its low infectivity to laboratory hosts and difficulties in obtaining defined cloned populations. The recent isolation of mouse-infectiveT. vivaxhas partially overcome the first problem. We have developed a highly efficient cloning technique which has been applied to the isolation of a collection of 71 clones, representing 31 distinct variable antigen types, of mouse-infectiveT. vivaxfrom Nigeria. This serodeme showed no cross-reaction with severalT. brucei-group serodemes, but some cross-reaction with naturally occurring KenyanT. vivax.